Strategi Sustainability Strategy and The Role of Public Relations in the Promotion of Environmental Tourism Banten - Awaloedin, Dipa Teruna; Pradini, Gagih; Rohiyati, Ulfa Falahi; Andini, Davi Ayu (CV ODIS, 2024)
Sustainable tourism development encompasses aspects of nature, culture, heritage, and economics, presenting a complex challenge involving tourists and local communities as hosts. This responsibility for preserving the environment falls on stakeholders, especially those in tourism planning and development. Environmental sustainability benefits local communities and enhances tourist experiences by maintaining natural beauty and culture, increasing income opportunities, and improving quality of life. Effective tourism management is crucial for attracting and retaining tourists. The study examines why certain attractions gain media attention, collaborating with public relations firms to disseminate reliable information. Public relations is vital in connecting producers with consumers and shaping public opinion. The study aims to explore public relations strategies in tourism promotion, special events, product development, and collaboration with the public, providing insights into their efficacy. Qualitative methods are employed to understand the cases comprehensively. The role of public relations in achieving institutional goals is crucial, using strategies like social, persuasive, and educational approaches. Public relations combines marketing mix with public relations to stimulate customer sales, which is essential in promoting tourism objects with excellent service and optimal management. Various media, including mass media and organisational publications, are utilised to disseminate tourism information effectively. The